Improved Framework Conditions for a More Entrepreneurial, Innovative and Sustainable EU - Niklas Elert; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2021)
In the wake of the corona crisis, the European Union must regain lost ground and create more favorable conditions for inclusive and sustainable economic growth. The best way to achieve this goal is by increasing the Union's innovativeness. This effort requires extensive and broad-based institutional reforms aimed at strengthening the incentives for entrepreneurship. Innovative entrepreneurship requires collaborations with numerous agents that provide those skills and resources that the entrepreneur is lacking: inventors, key personnel, demanding customers, and early and later-stage financiers. Based on this ecosystem perspective, we propose reforms in the following six broad areas: (i) the rule of law and property rights, ii) taxation, iii) savings and finance, iv) labor market regulations and social security, v) entry and exit barriers in product markets, and (vi) human capital for entrepreneurship. The reforms would likely strengthen Europe's innovation capacity at a time when it is needed more than ever.
Keywords: L26; L5; M13; O38; O52; P14; 330; Entrepreneurship; European Union; Innovation; Institutions; Policy reform; Regulation; Self-employment